Measuring twenty-first century skills: development and validation of a scale for in-service and pre-service teachers. Issue 2 (14th March 2016) - Jia, Yueming; Oh, Youn Joo; Sibuma, Bernadette; LaBanca, Frank; Lorentson, Mhora
Abstract : A self-report scale that measures teachers' confidence in teaching students about twenty-first century skills was developed and validated with pre-service and in-service teachers. First, 16 items were created to measure teaching confidence in six areas: information literacy, collaboration, communication, innovation and creativity, problem solving, and responsible citizenship. Then, the items were tested in two groups of pre-service teachers and two groups of in-service teachers respectively. Exploratory factor analyses and confirmatory factor analyses were conducted to examine the scale's validity and reliability. The analyses identified a three-construct scale including innovation and problem solving, collaboration, and utility of technology for pre-service teachers and a one-dimension scale, cross-functional skills, for in-service teachers. This study suggests that different scales should be used to measure in-service teachers' and pre-service teachers' confidence in teaching twenty-first century skills.